Surface Oxygen Vacancies: Dynamics of Photo‐Induced Surface Oxygen Vacancies in Metal‐Oxide Semiconductors Studied Under Ambient Conditions (Adv. Sci. 22/2019). Issue 22 (20th November 2019) - Glass, Daniel; Cortés, Emiliano; Ben‐Jaber, Sultan; Brick, Thomas; Peveler, William J.; Blackman, Christopher S.; Howle, Christopher R.; Quesada‐Cabrera, Raul; Parkin, Ivan P.; Maier, Stefan A.
Abstract : Surface oxygen vacancy defects are some of the most reactive sites but are notoriously difficult to detect, often healing upon exposure to air. In article number 1901841, Ivan P. Parkin, Stefan A. Maier, and co‐workers show how photo‐induced enhanced Raman spectroscopy (PIERS) can be used to indirectly track vacancy formation and healing of photo‐induced vacancies under ambient conditions on metal oxide semiconductors.